Spring migration of red knots along the Virginia barrier islands. Issue 2 (11th December 2014) - Watts, Bryan D.; Truitt, Barry R.
ABSTRACT We conducted low‐altitude, aerial surveys from the last week of April through the first week of June (1995, 1996, 2005–2013) to assess patterns in bird abundance, migration phenology, and habitat use of red knots (Calidris canutus rufa) staging along the Virginia barrier islands. During most years, knots arrived in early May, reached peak abundance during the third week of May, and were gone by mid‐June. The peak period (10 May–3 June) accounted for >90% of detections for all years. The mean high count during the study was 7, 373 ± 407 (SE). Decadal comparisons of high counts, accumulated numbers for the period of peak abundance and the season totals provided mixed results. Knots within the study area used peat banks and sandy beaches for foraging. Intertidal peat banks were patchily distributed and represented only 6% of the shoreline. Mean knot densities were comparable between the 2 habitats in the early period of migration but diverged rapidly such that by the third week of May, knot densities were 10‐fold higher on peat compared to sand. Knots exhibited wide annual variation in habitat use; the number of knots observed on peat varied from 13% to 91% of the total birds for a given year, presumably reflecting the underlying population dynamics of respective bivalve populations. Potential prey dynamics coupled with the patchy distribution of peat appear to cause year‐to‐year variation in space use along the island chain. The Virginia barrier islands appear to be part of a terminal staging area for red knots that stretches from New Jersey south through the Outer Banks of North Carolina. Documenting red knot use within portions of this region beyond the well‐studied Delaware Bay may lead to a more complete understanding of the sampling process used by red knots to make staging decisions. © 2014 The Wildlife Society.